A pilot study on development and feasibility of the ‘MyEducation: CABG application’ for patients undergoing coronary artery bypass graft (CABG) surgery - Noor Hanita, Z; Khatijah Lim, Abdullah *; S., Kamaruzzaman; Karuthan, Chinna; R. A. Raja, Mokhtar (BMC, 2022)
Background: Patients scheduled for coronary artery bypass graft (CABG) surgery tend to have persistent symptoms of anxiety and depression. Course of hospital stay post-CABG procedure has become increasingly shorter over the last few decades. This pilot study was conducted to develop and test feasibility of MyEducation: CABG application as a learning tool to reduce anxiety and depression levels among patients undergoing CABG Surgery.